2019
DOI: 10.1016/j.molp.2019.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous Hypoxia in Lateral Root Primordia Controls Root Architecture by Antagonizing Auxin Signaling in Arabidopsis

Abstract: As non-photosynthesizing organs, roots are dependent on diffusion of oxygen from the external environment and, in some instances, from the shoot for their aerobic metabolism. Establishment of hypoxic niches in the developing tissues of plants has been postulated as a consequence of insufficient diffusion of oxygen to satisfy the demands throughout development. Here, we report that such niches are established at specific stages of lateral root primordia development in Arabidopsis thaliana grown under aerobic co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
105
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(111 citation statements)
references
References 78 publications
3
105
3
Order By: Relevance
“…In addition, as both O 2 and NO promote ERFVII proteolysis 17 , and since ethylene was administered at ambient O 2 conditions (21%; normoxia) and did not lead to hypoxia in desiccators (Supplementary Figure 7c), it is unlikely that hypoxia causes the observed ERFVII stabilization. Furthermore, while recent reports show that plants contain a hypoxic niche in shoot apical meristems and lateral root primordia 25,26 , we did not observe enhanced hypoxia target gene expression in root tips exposed ethylene treatments (Supplementary Figure 5), ruling out ethylene-enhanced local hypoxia in these tissues.…”
Section: Resultscontrasting
confidence: 80%
“…In addition, as both O 2 and NO promote ERFVII proteolysis 17 , and since ethylene was administered at ambient O 2 conditions (21%; normoxia) and did not lead to hypoxia in desiccators (Supplementary Figure 7c), it is unlikely that hypoxia causes the observed ERFVII stabilization. Furthermore, while recent reports show that plants contain a hypoxic niche in shoot apical meristems and lateral root primordia 25,26 , we did not observe enhanced hypoxia target gene expression in root tips exposed ethylene treatments (Supplementary Figure 5), ruling out ethylene-enhanced local hypoxia in these tissues.…”
Section: Resultscontrasting
confidence: 80%
“…NAC060, has been shown to be induced by the sugar-ABA signalling pathway. However, NAC060 availability in the nucleus hinders sugar-ABA signalling leading to seedlings' insensitivity to sugars 65 . A former study in rice showed that the link between low oxygen signals and the sugar-sensing cascade (via SnRK1) is important for regulation of sugar and energy production and therefore rice growth under flood conditions 66 .…”
Section: Regulated Transcription Factors Serve As Potential Targets Fmentioning
confidence: 99%
“…There is therefore a link between osmotic and oxidative stress, root formation and the activity of this group of genes. It has recently been shown that hypoxic niches are generated during the formation of lateral roots in Arabidopsis, which leads to the induction of ERF-VII genes, which in turn modulate the auxin response in the developing tissue (Shukla et al 2019). Moreover, this hypoxic environment has also been detected in the shoot apical meristem, where oxygen acts as a diffusible signal that controls development (Weits et al 2019).…”
Section: Discussionmentioning
confidence: 99%